Compsoctena pulla sp. nov. a new species of Eriocottidae, Compsocteninae from Thailand (Lepidoptera) - Sobczyk, Thomas; Breithaupt, Roland (Zootaxa, 2023)
Compsoctena pulla sp. nov. is described. It is the first species of subfamily Compsocteninae (Lepidoptera: Eriocottidae) from Thailand. Male, female, venation and genitalia are depicted.